MOLECULAR MECHANISM OF HUMAN NRF2 ACTIVATION AND DEGRADATION: ROLE OF SEQUENTIAL PHOSPHORYLATION BY PROTEIN KINASE CK2 - Pi, Jingbo (2007)
Nrf2 is a key transcription factor in the cellular response to oxidative stress. In this study we first identify two phosphorylated forms of endogenous human Nrf2 after chemically-induced oxidative stress and provide evidence that protein kinase CK2-mediated sequential phosphorylation plays potential role in Nrf2 activation and degradation. Human Nrf2 has a predicted molecular mass of 66 kDa. However, immunoblots showed that two bands at 98 and 118 kDa, which are identified as phosphorylated forms, are increased in response to Nrf2 inducers. In addition, human Nrf2 was found to be a substrate for CK2 which mediated two steps of phosphorylation, resulting in two forms of Nrf2 migrating with differing Mr at 98 kDa (Nrf2–98) and 118 kDa (Nrf2–118). Our results support a role in which calmodulin binding regulates CK2 activity, in that cold (25 °C) in Ca(2+)-free media (cold/Ca(2+)-free) decreased both cellular calcium levels and CK2-calmodulin binding and induced Nrf2–118 formation, the latter of which was prevented by CK2 specific inhibitors. Gel-shift assays showed that the Nrf2–118 generated under cold/Ca(2+)-free conditions does not bind to the antioxidant response element, indicating that Nrf2–98 has transcriptional activity. In contrast, Nrf2–118 is more susceptible to degradation. These results provide evidence for phosphorylation by CK2 as a critical controlling factor in Nrf2-mediated cellular antioxidant response.